(untitled) (Global Journal of Management and Business Research, 2019)
Extrinsic rewards remain significant for employees, although their effect on career sustainability, especially among the tours and travel company employees, is still missing in research. This study was carried out in Mombasa County, located in the South-Eastern part of the Coastal region of Kenya. It utilizes a mixed-methods design comprising of a combination of qualitative and quantitative research components. From a total population of 2800 employees in the travel and tour companies, this study used proportionate sampling to select respondents comprised of 20 finance officers, 92 marketing officers, 46 operations officers, and 192 driver or tour guides formed the sample size. The study uses Pearson correlation and multivariate regression analysis to test the significant relationships between extrinsic motivation and career sustainability. There was a positive relationship between extrinsic motivations and career sustainability [r = .615, n = 346, p